2021
DOI: 10.28945/4746
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Determinants of Wearable Payment Adoption: An Empirical Study

Abstract: Aim/Purpose: The aim of this study is to determine the variables which affect the intention to use Near Field Communication (NFC)-enabled smart wearables (e.g., smartwatches, rings, wristbands) payments. Background: Despite the enormous potential of wearable payments, studies investigating the adoption of this technology are scarce. Methodology: This study extends the Technology Acceptance Model (TAM) with four additional variables (Perceived Security, Trust, Perceived Cost, and Attractiveness of Alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 169 publications
0
5
0
Order By: Relevance
“…Hong et al (2006) and Dia et al (2020) reported that a user's perceived PE of a technology is a key determinant of satisfaction and continuance intention. Prior studies reported the significant positive effect of PE on satisfaction (e.g., Joo et al, 2016;Kim-Soon et al, 2017;Kumar et al, 2018;Lim et al, 2019), and continuous intention to use a technology (e.g., Foroughi et al, 2019;Gilani et al, 2017;Rabaai, 2015;Rabaai et al, 2015;Rabaa'i, 2016Rabaa'i, , 2017bRabaa'i and Zhu, 2021;Rabaa'i, in press;Shaw & Sergueeva, 2019;. Additionally, previous studies also confirmed the significant relationship between PE and users' attitude (e.g., Dai et al, 2020;Ding, 2019;Gasaymeh & Waswas, 2019;Ifinedo, 2018;Sabah, 2019).…”
Section: Figure 1 the Ecm (Bhattacherjee 2001a)mentioning
confidence: 68%
“…Hong et al (2006) and Dia et al (2020) reported that a user's perceived PE of a technology is a key determinant of satisfaction and continuance intention. Prior studies reported the significant positive effect of PE on satisfaction (e.g., Joo et al, 2016;Kim-Soon et al, 2017;Kumar et al, 2018;Lim et al, 2019), and continuous intention to use a technology (e.g., Foroughi et al, 2019;Gilani et al, 2017;Rabaai, 2015;Rabaai et al, 2015;Rabaa'i, 2016Rabaa'i, , 2017bRabaa'i and Zhu, 2021;Rabaa'i, in press;Shaw & Sergueeva, 2019;. Additionally, previous studies also confirmed the significant relationship between PE and users' attitude (e.g., Dai et al, 2020;Ding, 2019;Gasaymeh & Waswas, 2019;Ifinedo, 2018;Sabah, 2019).…”
Section: Figure 1 the Ecm (Bhattacherjee 2001a)mentioning
confidence: 68%
“…As an emerging theme, DeFi intersects with blockchain, smart contracts, regtech, big data, digital wallets, peer‐to‐peer lending, e‐insurance, open banking, atomic swaps, autonomous liquidity pools, decentralized stablecoins, and flash loans (Aspris et al, 2021; Jiao et al, 2021; Zetzsche et al, 2020). DeFi's objective is to democratize finance by replacing centralized intermediaries, such as banks, exchanges, and insurers, with peer‐to‐peer relationships for greater efficiency and transparency on the full spectrum of BFSI products and services (Hamayel et al, 2021; Li et al, 2021; Nagar et al, 2021; Osakwe et al, 2021; Rabaa'i & Zhu, 2021). This democratization is particularly important to small and medium enterprises and family businesses, who have been dictated payment terms by larger entities in the supply chain (Crowe, 2020).…”
Section: Into the Futurementioning
confidence: 99%
“…DeFi's objective is to democratize finance by replacing centralized intermediaries, such F I G U R E 1 2 Strategic diagram for the 2017-2018 period, sphere size denotes the total citations count (source: Authors, based on SciMAT visualization). as banks, exchanges, and insurers, with peer-to-peer relationships for greater efficiency and transparency on the full spectrum of BFSI products and services (Hamayel et al, 2021;Li et al, 2021;Nagar et al, 2021;Osakwe et al, 2021;Rabaa'i & Zhu, 2021). This democratization is particularly important to small and medium enterprises and family businesses, who have been dictated payment terms by larger entities in the supply chain (Crowe, 2020).…”
Section: Decentralized Financementioning
confidence: 99%
“…They only focused on technological factors and overlooked external factors such as social influence. Rabaa'i and Zhu 13 conducted research on similar adoption factors in Kuwait, integrating trust, but they did not consider external factors and indirect relationships (mediation and moderation) in their research framework. However, few empirical studies based on mobile payment usage 14 , 15 and the adoption of wearable technologies 16 were conducted in Malaysia.…”
Section: Introductionmentioning
confidence: 99%